Clinical and Laboratory Characteristics of Acute Kidney Injury in Critically Ill Children: A Single Center Study - Faeghe Baryar Langroudi; Hamid Mohammadjafari; Hani Rostami Rad; Mohaddeseh Momeni; Maedeh Guran; Mohammad Reza Navaeifar (Mazandaran University of Medical Sciences, 2023)
Background: Acute kidney injury stands out as one of the common complications in the pediatric intensive care unit.  Objectives: This study was designed to evaluate acute kidney injury's frequency, etiologies, and its course in critically ill children. Methods: This cross-sectional study was conducted in a tertiary training pediatric intensive care unit. The definition of acute kidney injury is based on the pRIFLE (pediatric risk, injury, failure, loss, end stage renal disease). Analysis of possible variables contributing to acute kidney injury was made using data up to 48 hours before the onset of renal failure. Results: In 255 patients analyzed, the median age was 18 (IQR, 6-60) months. The common causes of admission were infectious diseases (50.2%) and neurologic disorders (25.9%). Acute kidney injury occurred in 63 patients (24.7%). Prerenal acute kidney injury occurred in 43 patients (68.3%), renal in 11(17.5%), postrenal in 2(3.2%), and 7(11.1%) were unspecified. Patients with the risk, injury, failure, and loss stages of the pRIFLE definition were 40(63.5%), 14(22.2%), 6(9.5%), and 3(4.8%), respectively. The length of hospital stay was significantly higher in acute kidney injury patients (P=0.041). After controlling for other risk factors, acute kidney injury was higher in patients with lower age, higher PRISM (pediatric risk of mortality) III scores, multiple organ dysfunction, leukocytosis, hypernatremia, and acidosis (P<0.05). Conclusions: Acute kidney injury is a significant concern in pediatric intensive care units, which contributes to prolonged hospital stay. The lower age, higher mortality scores, multiple organ dysfunction, leukocytosis, hypernatremia, and acidosis are risk factors for the next 48 hours of acute kidney injury.